Associations of Lifestyle Patterns With Overweight and Depressive Symptoms Among United States Emerging Adults With Different Employment Statuses - Qian-Wen Xie; Qian-Wen Xie; Qian-Wen Xie; Xu Li Fan; Xiangyan Luo; Jieling Chen (Frontiers Media S.A., 2023)
Objective: To identify lifestyle patterns in emerging adults and examine the association of lifestyle patterns with overweight and depression.Methods: Data was from the National Health and Nutrition Examination Survey between 2011 and 2018. A latent class analysis (LCA) was conducted with 2,268 US emerging adults based on sedentary behavior, moderate-to-vigorous physical activity, diet, sleep, alcohol drinking, and cigarette smoking. The associations of lifestyle groups with overweight and depression were examined by logistic regression and were further stratified by employment status.Results: The LCA results favored a four-class solution: "unhealthy but non-substance use" (59%), "healthy but sleepless and drinking" (12%), "unhealthy lifestyle" (15%), and "healthy but sedentary" group (14%). Compared to the "unhealthy lifestyle" group, participants in the "unhealthy but non-substance use" (coef. = −1.44, SE = 0.27; OR = 0.40, 95% CI [0.26, 0.61]), "healthy but sleepless and drinking" (coef. = −1.49, SE = 0.35; OR = 0.38, 95% CI [0.20, 0.72]), and "healthy but sedentary" (coef. = −1.97, SE = 0.34; OR = 0.29, 95% CI [0.14, 0.57]) groups had lower depression severity and reported fewer depressive symptoms. Moreover, lifestyle groups and health outcomes showed different relationships among employed and unemployed participants.Conclusion: This study found that the combinations of lifestyle behaviors had synergistic effects on mental health, and such effects differed by employment status.